Producing a village input-output table (VIOT) from household survey data: A case study of a VIOT for a rural village in northern Lao PDR - Soulixay Hongsakhone; Moinul Islam; Masaru Ichihashi (Journal of Economic Structures, 2021)
In this study, a village input-output table (VIOT) is built from household survey data from a rural village in a developing country to capture the interdependency between households through their transactions in 2016. This VIOT is a simple, but useful tool for understanding the economic transactions among villagers. The main findings of this work are that lower- and middle-income households mainly depend on commodities supplied by non-poor counterparts, especially by four higher-income households, who are not only producers, but also traders of commodities in the village and play key roles in the village economy, and that the IO interdependency among non-poor households is stronger than that among poor households. Additionally, this paper describes a first trial application of the VIOT method to develop economic policies with goals such as poverty reduction and trade expansion in the village.
Keywords: D13; D57; I32; O13; R15; 330; Economic development; Inter-household dependency; Transactions; Village input-output table